Investigation into participation of annexins in the response of Arabidopsis thaliana roots to lead (Pb) exposure: Preliminary study - Phang, Ing Chia (2007)
As shown in previous studies, annexins are involved in many essential cellular processes and defence against various types of biotic and abiotic stresses. The purpose of this study is primarily to assess the relative contribution of annexins in the antioxidative defence against lead (Pb) stress. It is hypothesized that Pb exposure could result in oxidative burst in Arabidopsis thaliana, particularly the roots, which are in direct contact with the heavy metal. This new insight of how annexins might be involved in Pb tolerance of plant cells will pave way to the development of phytoremediation technology based on this green plants’ ability to remove Pb from the environment in a cost-efficient and ecologically sound manner. The initial correlative studies included studies on the effect of Pb on plant growth, determination of Pb content in plant material, ultrastructural localization of Pb within plant cells, and antioxidative enzyme assays. The severity of these responses increased with increasing concentrations of Pb. On the other hand, the initial manipulative studies showed that the interaction of NO with reactive oxygen species acts as a protective mechanism in Pb stress. All these preliminary experiments will further support the role which annexins could play in the response of plants to heavy metal stress in order to protect the cells from the stress. Primers for annexin 1 (AnnAt1) have been obtained and testing for RT-PCR is now underway.